2012
DOI: 10.1074/jbc.m112.348383
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor Activation of Human Cells by Synthetic Triacylated Lipid A-like Molecules

Abstract: Background: Binding of LPSs and lipopeptides to Toll-like receptors depends on their lipid moieties. Results: Synthetic triacylated LPS-like molecules bind to TLR2 (weak agonists) and TLR4 (strong antagonists) and block phagocytosis of Gram-negative bacteria. Conclusion: Triacylated LPS-like molecules are potent TLR4 antagonists. Significance: These compounds may represent valuable LPS antagonists and immunomodulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Epidemiological studies showed a correlation between immunological parameters and long-term survival in neoplastic patients [11]. Immunotherapeutic approaches based on the use of bacterial components such as the BCG or a lipid A derivative of LPS (OM-174-DP) have been proposed to increase the efficacy of standard treatments in different malignances including ovarian cancer [30,31]. It is of note however, that our present data, together with previous studies, suggest the existence of a complex tumor microenvironment that would impair the attack of immune effectors such as NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies showed a correlation between immunological parameters and long-term survival in neoplastic patients [11]. Immunotherapeutic approaches based on the use of bacterial components such as the BCG or a lipid A derivative of LPS (OM-174-DP) have been proposed to increase the efficacy of standard treatments in different malignances including ovarian cancer [30,31]. It is of note however, that our present data, together with previous studies, suggest the existence of a complex tumor microenvironment that would impair the attack of immune effectors such as NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first step required for LPS to exert its direct BBB-disrupting effect is through binding to LPS receptors at the BBB, mainly mediated by the lipid A component of LPS (41). Therefore, the reason for the difference in the specific BBB-disrupting effect of S. enterica LPS relative to that of P. aeruginosa LPS may be differences in their structures, especially the lipid A component of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…A further example of a synthetic LPS derivative is a symmetric lipid A mimetic consisting of two glucose residues linked through a (6→6′) succinic diamide linker, with two sulfate groups in place of the phosphate moieties, which was found to bind MD‐2 and to compete successfully with toxic LPSs . This small number of examples represents the tip of the iceberg of the vast potential for therapeutic applications of compounds with antagonistic activity inspired by natural LPSs . In this context, the observation of very low or no immunostimulatory effects exerted by some LPSs isolated from several extremophile bacteria, in addition to the quasi‐infinite sources from which it is possible to isolate such microorganisms, constituted an indubitable incentive to intensify the research into LPS antagonist candidates.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%